Arquitectura y naturaleza : Tigre - Roca, Miguel Angel; Narvaez, Eduardo; Grinberg, Horacio; Ruiz Orrico, Juan; Villasuso, Víctor
Reflexión y propuesta para el Tigre.
Keywords: ARGENTINA; BUENOS AIRES (PROV); TIGRE; PLANES URBANISTICOS; BARRIOS PERIFÉRICOS